2003
DOI: 10.1021/jf030607+
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Fusarium 2-Gene Cluster Involved in Trichothecene C-8 Modification

Abstract: The Fusarium trichothecenes T-2 toxin and deoxynivalenol (DON) are potent inhibitors of eukaryotic protein synthesis and are a significant agricultural problem. Three coregulated loci are required for T-2 toxin synthesis by Fusarium sporotrichioides. The core-trichothecene gene cluster consists of 12 genes (Tri3-Tri14) while the second locus consists of a single gene (Tri101). The third locus was recently partially described and encodes 1-2 biosynthetic enzymes and a putative regulatory gene. Here, we describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 28 publications
1
51
0
Order By: Relevance
“…the genes for trichothecene biosynthesis are split between three coregulated loci including a core cluster of 10 or 11 genes (3), a two-gene minicluster (4), and a third locus with a single trichothecene gene (Tri101) (15). Genes in the outlying miniclusters appear to have been recruited for trichothecene biosynthesis more recently than those in the core cluster, and Tri101 appears to have evolved separately, suggesting that these genes have never been located at a single locus (4,16). The physical arrangement of atm genes in A. flavus and A. oryzae is likely to have arisen by fragmentation of a single ancestral cluster.…”
Section: Discussionmentioning
confidence: 99%
“…the genes for trichothecene biosynthesis are split between three coregulated loci including a core cluster of 10 or 11 genes (3), a two-gene minicluster (4), and a third locus with a single trichothecene gene (Tri101) (15). Genes in the outlying miniclusters appear to have been recruited for trichothecene biosynthesis more recently than those in the core cluster, and Tri101 appears to have evolved separately, suggesting that these genes have never been located at a single locus (4,16). The physical arrangement of atm genes in A. flavus and A. oryzae is likely to have arisen by fragmentation of a single ancestral cluster.…”
Section: Discussionmentioning
confidence: 99%
“…TRI6 is a DNA-binding regulatory protein that acts as a positive regulator of trichothecene biosynthesis . All previously characterized TRI structural genes, located within and outside the core cluster, have TRI6 binding sites in their promoter regions (Brown et al, 2001(Brown et al, , 2003McCormick et al, 1999). Second, Northern blot analysis using hybridization probes to all 12 ORFs indicate that they do not exhibit the same pattern of expression as genes located within (e.g., TRI5) or outside (e.g., TRI1 and TRI16) the trichothecene gene cluster.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Gibberella fujikuroi gibberellin biosynthetic genes P450-1 and P450-4 encode monooxygenases that catalyze 4 and 3 biosynthetic steps, respectively (Helliwell et al, 2001;Tudzynski et al, 2002). TRI11, TRI13, and TRI1 are unlikely multifunctional candidates because gene deletion studies clearly indicated that their proteins catalyze single steps later in the pathway (Alexander et al, 1998;Brown et al, 2003;Hohn et al, 1995). Interestingly, TRI4 transcripts are 8 times more abundant than the three other trichothecene P450 monooxygenases (Table 5) in the F. sporotrichioides EST library.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations